Studi Kapasitas Hubung Singkat Satu Fasa Ke Tanah Pada Penyulang 5 PT PLN (Persero) UP3 Tarakan - Ardi Setyo Purnomo; Achmad Budiman (Elektrika Borneo, 2021)
This study uses the etap 12.6.0 application to simulate the power flow using the Newton Rapshon method and uses the impedance method to determine the single-phase short circuit current to the ground in the 5 feeder. 1820 A, on the out going village 4 side, the largest disturbance current value is obtained on bus 112 of 2008 A, and on the out going charity side, the largest disturbance current value on bus 10 is 1734 A. out going results in feeders 5 of 0.330 MVA, out going for charity is 0.322 MVA and out going in village 4 is 0.347 MVA, at capacity of circuit breakers, results in feeders 5 are 0.24 MVA and out going charity is 0.213 The MVA and in out going village 4 were 0.213 MVA, the results exceeded the capacity of the existing circuit breakers, so what? if there is a single phase fault to ground in feeder 5 it will result in damage to the circuit breaker installed.